Risk perception of cardiovascular diseases among individuals with hypertension in rural Malaysia - Mohd Azahar, Nazar Mohd Zabadi (Heart Asia, 2017)
OBJECTIVE: Despite various efforts, hypertension remains poorly controlled, thus allowing cardiovascular disease (CVD) to impact the health burden worldwide. Patients’ perception of risk may contribute to this scenario. The present study aims to assess the level of risk perception among individuals with hypertension in rural Malaysia. METHODS: This is a community-based study conducted among adults between 2010 and 2011 among a rural population in Raub, Pahang, Malaysia. Blood pressure was measured after 5 min of rest. Measurement was done twice and the average was recorded. Cardiovascular risk perception score (CvRPS) was derived using the Modified Risk and Health Behavior Questionnaire. Higher CvRPS indicates the respondent perceives a poorer prognostic outlook. RESULTS: A total of 383 respondents who have hypertension participated in this study. The mean age of respondents was 62±10.6 years; men 63.1±9.6 years, women 61.2±11.1 years (p>0.05). Among hypertensives, those who were not on medication had significantly lower CvRPS compared with those who were on medications (115.9±22.1vs 120.9±23.5, p=0.036); those who were not aware of their hypertensive status had significantly lower CvRPS compared with respondents who were aware about their hypertension (116.7±22.5vs 121.7±21.3, p=0.029) and those with uncontrolled hypertension had significantly lower CvRPS compared with those whose blood pressure was controlled (118.2±22.2vs 128.8±25.8, p=0.009). CONCLUSIONS: Our study shows that respondents who were not on medications, unaware of their hypertension status and those who had uncontrolled hypertension tended to underestimate (lower CvRPS) their risk for CVD. Improving their CvPRS through a concerted health education may lead to better therapeutic behaviour and outcomes.